Multimedia : diverse approaches to complexities - Foreman, Nelly, editor (New Jersey : Clanrye International, 2015)
This book discusses the state-of-the-art information on multimedia and its diverse approaches. The current universal effortless digital data capture and processing capabilities presented by the majority of devices, lead to an exceptional intrusion of multimedia content in our day-to-day life. To make the most of this phenomenon, the swiftly escalating volume and utilization of digitized content needs continuous re-examination and adaptation of multimedia methods, for the purpose of meeting the relentless change of necessities from both the user and system viewpoints. Developments in multimedia give readers an analysis of the ever-growing field of multimedia by integrating several research analyses and surveys from distinct subfields that point out such significant aspects. Certain major topics encompassed in this book are security characteristics in multimedia, latest multimedia applications, multimedia management in peer-to-peer structures & wireless networks, and semantic gap bridging for multimedia content.